Perioperative nutritional management for patients with hepatobiliary tumours: a mini review - Haoran Wu; Zhongxian Guo; Huimin Song; Lu Wang; Yuli Gou; Shixiao Jin; Zhongying Huang; Liyan Sha (Holistic Integrative Oncology)
Abstract Surgical resection and liver transplantation are the first-line treatments for the treatment of hepatobiliary tumours. However, owing to the prevalence of tumour-related diseases and malnutrition among surgical patients, the incidence of postoperative complications is relatively low in terms of immune function. Providing patients with scientific and appropriate nutritional management during the perioperative period can enhance their nutritional status, accelerate postoperative recovery, reduce the risk of complications, and enhance the body's tolerance. Perioperative nutritional management can improve the nutritional status of patients and improve their tolerance, which plays an important role in their survival and prognosis. This article is based on the 6s evidence resource pyramid model, and systematically searches major databases, professional guide websites, and nutrition related platforms at home and abroad from top to bottom to obtain literature on perioperative nutrition management for patients with liver and gallbladder tumors. After deduplication and literature quality evaluation screening. This article reviews the status quo of nutritional diagnosis, nutritional intervention, nutritional health guidance, and follow-up in patients with hepatobiliary tumours during the perioperative period. The aim is to improve the nutritional status of patients by medical staff, provide more perfect dietary management strategies for patients, and accelerate their rehabilitation.